Determinasi Nilai Perusahaan pada Perbankan Konvensional di Indonesia - Lazuardi K, Prasetia; Wiratno, Adi (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2023)
In this study, it has a goal to show whether Liquidity, Profitability, and Operational Efficiency have an influence on Firm Value in Banking. To prove the inconsistency of previous research results regarding several independent variables used. This study used 10 banking samples at Buku4 banks through a purposive sampling method. Secondary data will be used for research, where this data is taken from the annual reports of banks listed on the Indonesia Stock Exchange (IDX). Data processing in this study uses the EViews ver. 9. The results of this study show that liquidity has a negative effect on firm value. While profitability and operating efficiency have a positive effect on firm value. These findings provide answers regarding the importance of banking in maintaining its level of profitability. In addition, banks must also maintain efficiency so that the funds used can be maintained so that the company can be sure to have very good value. Meanwhile, banks may not have too much idle capital, it can cause a decrease in the value of the Company.